G323(P) A case of shingles with no history of chicken pox. (12th March 2018) - Butt, A; Sinha, G
Abstract : Introduction: Herpes Zoster Ophthalmicus (HZO) is a specific form of shingles that affects the dermatome of the ophthalmic nerve. It can have serious sequelae including permanent visual loss if there is ocular involvement. Case report: A 20-month-old child presented to the Paediatric Assessment Unit with a vesicular rash on his left forehead, and with swelling around the left eye. He had been treated with Flucloxacillin for impetigo, however this had failed to resolve the rash. He was apyrexial, passing urine and stool normally but had decreased oral intake. On examination the rash was restricted to the territory of the left ophthalmic nerve. The left eye was swollen with a yellow discharge and could not be opened. Swabs from the eye, and of the vesicular fluid were sent for bacterial culture and viral PCR. Initial bloods, including FBC and CRP, were normal, with no evidence of systemic infection. A diagnosis of HZO was made, based on the clinical findings, and the child was commenced on IV Aciclovir, IV Co-Amoxiclav, and Chloramphenicol eye drops. The following day the child had developed a fever and was tachycardic and tachypnoeic; the antibiotics were converted into Ceftriaxone. Varicella zoster IgG was found to be positive suggesting past infection. Ophthalmological opinion was sought to rule out ocular involvement. They found the child to be Hutchison's sign negative and agreed with the diagnosis of HZO without ocular involvement. The child received 7 days of Aciclovir, 7 days of antibiotics and 14 days of Chloramphenicol eye drops. The bacterial culture later isolated Moraxella catarrhalis, and the viral PCR confirmed Varicella zoster DNA. Learning points: Asymptomatic chickenpox is uncommon, although mild cases may be missed. Chickenpox infection can occur in utero and can cause scarring, neurological and ophthalmic complications, or the baby can be asymptomatic and present in early life with shingles. Accurate diagnosis is important to prompt early management. Examination of the eye with Ophthalmological input is important to rule out or manage ocular involvement. Hutchison's sign indicates nasociliary branch involvement increasing the likelihood of ocular sequelae.